2010
DOI: 10.1038/ng.669
|View full text |Cite
|
Sign up to set email alerts
|

A locus on 19p13 modifies risk of breast cancer in BRCA1 mutation carriers and is associated with hormone receptor–negative breast cancer in the general population

Abstract: Germline BRCA1 mutations predispose to breast cancer. To identify genetic modifiers of this risk, we performed a genome-wide association study in 1,193 individuals with BRCA1 mutations who were diagnosed with invasive breast cancer under age 40 and 1,190 BRCA1 carriers without breast cancer diagnosis over age 35. We took forward 96 SNPs for replication in another 5,986 BRCA1 carriers (2,974 individuals with breast cancer and 3,012 unaffected individuals). Five SNPs on 19p13 were associated with breast cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
272
5
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 311 publications
(300 citation statements)
references
References 32 publications
(16 reference statements)
13
272
5
10
Order By: Relevance
“…and ER-disease [25,27]. On the other hand, variants in ESR1 and 19p13 show evidence of an association primarily with ER-BCs [20,[29][30][31]. At present, there are no data on possible correlations between clinicopathological characteristics and common low-penetrance BC susceptibility alleles in MBC.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…and ER-disease [25,27]. On the other hand, variants in ESR1 and 19p13 show evidence of an association primarily with ER-BCs [20,[29][30][31]. At present, there are no data on possible correlations between clinicopathological characteristics and common low-penetrance BC susceptibility alleles in MBC.…”
Section: Introductionmentioning
confidence: 62%
“…Genome-wide association studies (GWAS) have identified associations between single nucleotide polymorphisms (SNPs), acting as common lowpenetrance variant alleles, and BC risk in women [13][14][15][16][17][18][19][20][21]. An involvement of some of the SNPs found to be associated with FBC has been suggested in MBC susceptibility [22], and by GWAS we could recently identify a novel common variant associated with MBC [23].…”
Section: Introductionmentioning
confidence: 99%
“…GEMO is the French branch of the international initiative CIMBA (Consortium of Investigators of Modifiers of BRCA1 and BRCA2), which aims at identifying modifiers of breast cancer risk through the collection of DNA and clinical data from a large number of BRCA1 and BRCA2 mutation carriers. [12][13][14] Participation in the GEMO cohort was proposed during the cancer clinic in which patients were informed of a positive BRCA1/2 test result. Their written informed consent was obtained.…”
Section: Subjects and Methods Patientsmentioning
confidence: 99%
“…[75]. These are the same SNPs that provided independent evidence of association with breast cancer risk for BRCA1 mutation carriers, identified through the BRCA1 GWAS [40]. An analysis of the associations of these SNPs with breast and ovarian cancer risk simultaneously for BRCA1 mutation carriers found no significant evidence of association with ovarian cancer risk in BRCA1 mutation carriers [40].…”
Section: Genetic Modifiers Of Ovarian Cancer Riskmentioning
confidence: 99%